1981
DOI: 10.1016/0091-7435(81)90010-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a multiple treatment program and maintenance procedures on smoking cessation

Abstract: This study evaluated the efficacy of a multiple treatment smoking cessation program and three maintenance strategies. Phase I of the study involved 51 subjects who participated in a 5-day smoking cessation project. The program consisted of lectures, demonstrations, practice exercises, aversive smoking, and the teaching of self-control procedures. In Phase II, all subjects were randomly assigned to one of three maintenance conditions: a 4-week support group which offered an opportunity to discuss feelings and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…31,[34][35][36][37][38][39]63,67,69,72,[78][79][80]84,[86][87][88][89] urinary or saliva cotinine (six trials), 65,68,70,71,75,81 or saliva thiocyanate (one trial) 40 and nine trials 41,64,66,73,74,76,77,82,85 presented self-reported abstinence only. All studies used a parallel group design except one which was cluster randomised; 41 however, any dependency in the data due to clustering was found to be negligible and, therefore, this study was analysed with the others.…”
Section: Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…31,[34][35][36][37][38][39]63,67,69,72,[78][79][80]84,[86][87][88][89] urinary or saliva cotinine (six trials), 65,68,70,71,75,81 or saliva thiocyanate (one trial) 40 and nine trials 41,64,66,73,74,76,77,82,85 presented self-reported abstinence only. All studies used a parallel group design except one which was cluster randomised; 41 however, any dependency in the data due to clustering was found to be negligible and, therefore, this study was analysed with the others.…”
Section: Included Studiesmentioning
confidence: 99%
“…There were 14 studies in this category 41,[76][77][78][79][80][81][82][83][84][85][86][87][88] and Table 5 summarises these.…”
Section: Behavioural Interventions In Other Population Groupsmentioning
confidence: 99%
See 3 more Smart Citations